CONCENTRATION OF CHLOROPHYL-a IN THE SOLOK PULAU LAKE, TANJUNG BALAM VILLAGE, SIAK HULU SUB DISTRICT, KAMPAR DISTRICT, RIAU PROVINCE - Sirait, Petrus Juandatua; Simarmata, Asmika Harnalin; Sihotang, Clemens (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The Solok Pulau Lake is an oxbow lake that receive water from the Tangon and Kampar Rivers. To understand the concentration of chlorophyll-a in the lake, this research was conducted from January to February 2015 in Solok Pulau Lake. Water samples were collected from three station, namely station1 (in the inlet from the Tangon River, station2 in the middle of the lake and station3 in the inlet from the Kampar River). Water quality parameters measured were transparency, temperature, dissolved oxygen, depth, pH, velocity, nitrates and phosphates concentration. Results shown the chlorophyll-a concentration ranged from 0.013- 0.016 (μg/L), transparency of 42-50 cm, temperature 28.3-28.70C, dissolved oxygen 1.56 to 2.17 mg/L, depth 1.56 to 2.17 mg/L, pH 5.5 and velocity 15-16 cm/sec. Based on chlorophyll-a concentration, it can be concluded the Solok Pulau Lake was oligotrophic.Key words :chlorophyll-a, Solok Pulau Lake, water quality, Tangon River and Kampar River.